Toward a model of issue-selling by subsidiary managers in multinational organizations - Ling, Yan; Floyd, Steven W; Baldridge, David C (Journal of International Business Studies, 2005)
In multinational organizations, local market responsiveness is critical to the development of effective strategies. This responsiveness is expected to occur in part as the result of upward influence from local subsidiary managers, who represent the local culture and shift relevant priorities accordingly. Issue-selling – defined as directing top management's attention to particular issues and helping them understand such issues – is one important way in which subsidiary managers pursue upward influence. The purpose of this paper is to help multinational organizations better facilitate and exploit potentially valuable input from local subsidiary managers. To do so, we propose an acculturated view of issue-selling. More specifically, we argue that subsidiary managers socialized by different national cultures vary: (1) in the extent to which their intention to sell issues is influenced by various contextual cues; and (2) in their choice of selling strategies. These theoretical differences suggest that local subsidiary managers from different cultures will differ in the way they approach issue-selling and, in turn, in the way they influence the strategy-making process. The discussion traces the implications of this line of reasoning for future research on the influence of local subsidiary managers and, more generally, for research on the cultural embeddedness of the strategy process.